Bleaching intracoronal gigi insisif pertama pasca perawatan endodontik (Laporan Kasus) - Rosita Stefani (Fakultas Kedokteran Gigi Universitas Trisakti, 2022)
Background: Non-vital anterior tooth discoloration is a common concern in everyday clinics. Increased patient demand for affordable and excellent results makes bleaching treatment for discolored teeth one of the most popular treatment options. Bleaching offers a more conservative and aesthetic solution compared to treatments like dental crown. Objective: To restore the color of the upper right maxillary incisor after endodontic treatment using internal bleaching with 35% hydrogen peroxide. Case: A 22-year-old male patient came with a complaint of discoloration of upper right maxillary incisor. On clinical examination, upper right maxillary incisor was discolored. On radiographic examination, radiolucency was observed in the periapex. Endodontic treatment was performed with biomechanical preparation using circumferential filing technique and obturation of root canals using a thermoplastic injection technique. At the next visit, an intraoral photo was taken, and the color upper right maxillary incisor was determined using a shade guide. Intracoronal bleaching was performed using 35% hydrogen peroxide bleaching gel. After the color of upper right maxillary incisor has blend well, then the teeth were restored using a composite resin. Conclusion: Intracoronal bleaching treatment with 35% hydrogen peroxide is a conservative and aesthetic treatment to restore the color of the tooth with an excellent result.